Risk factors and prediction model of sleep disturbance in patients with maintenance hemodialysis: A single center study - Xu, Rongpeng; Miao, Liying; Ni, Jiayuan; Ding, Yuan; Song, Yuwei; Yang, Chun; Zhu, Bin; Jiang, Riyue (Frontiers in Neurology, 2022)
Objectives: This study aimed to explore the risk factors and develop a prediction model of sleep disturbance in maintenance hemodialysis (MHD) patients. Methods: In this study, 193 MHD patients were enrolled and sleep quality was assessed by Pittsburgh Sleep Quality Index. The risk factors of sleep disturbance in MHD patients were evaluated, and that a prediction model was developed on the basis of risk factors. Results: The prevalence of sleep disturbance and severe sleep disturbance in MHD patients was 63.73% and 26.42%, respectively. Independent risk factors for sleep disturbance in MHD patients included higher 0.1*age (OR = 1.476, 95% CI: 1.103-1.975, P = 0.009), lower albumin (OR = 0.863, 95% CI: 0.771-0.965, P = 0.010), and lower 10*calcium levels (OR = 0.747, 95% CI: 0.615-0.907, P=0.003). In addition, higher 0.1*age, lower albumin levels, and anxiety were independently associated with severe sleep disturbance in MHD patients. A risk prediction model of sleep disturbance in MHD patients showed that the concordance index after calibration is 0.736, and the calibration curve is approximately distributed along the reference line. Conclusions: Higher age, lower albumin and calcium levels are higher risk factors of sleep disturbance in MHD, and the prediction model for the assessment of sleep disturbance in MHD patients has excellent discrimination and calibration.